Fluid dynamics in the functional foregut of xylem-sap feeding insects: A comparative study of two Xylella fastidiosa vectors. (January 2020) - Ranieri, Emanuele; Zitti, Gianluca; Riolo, Paola; Isidoro, Nunzio; Ruschioni, Sara; Brocchini, Maurizio; Almeida, Rodrigo P.P.
Graphical abstract: Highlights: Foregut morphometry of leafhopper and spittlebug performed with μCT and SEM. Foregut hydrodynamics reproduced through CFD modeling. The foregut of the spittlebug may harbor twice as many X. fastidiosa cells as the leafhopper. Sap velocity in the foregut is 10 cm/s if only 5% of the cibarium volume is exploited. Bacterial colonization may impact sap ingestion of a leafhopper more than the spittlebug. Abstract: Xylem sap sucking insects are adapted to ingest fluids under tension. Although much has been learned about such feeding strategy, this adaptation still poses several unresolved questions, including how these insects ingest against strong xylem sap tension. Xylem sap-feeding insects are vectors of the plant pathogenic xylem-limited bacterium Xylella fastidiosa . This bacterium colonizes the cuticular lining of the foregut of vectors in a persistent manner. We used micro-computed tomography and scanning electron microscopy to investigate the foregut morphometry of two X. fastidiosa vector species: Philaenus spumarius and Graphocephala atropunctata (Hemiptera: Aphrophoridae and Cicadellidae, respectively). On the basis of morphometric data, we built a hydrodynamic model of the foregut of these two insect species, focusing on the precibarium, a region previously shown to be colonized by X. fastidiosa and correlated with pathogen acquisition from and inoculation to plants. Our data show that space in the P. spumarius functional foregut could potentially harbor twice as many cells as similar space in G. atropunctata, although the opposite trend has been observed with biological samples. Average flow velocity of ingested fluid depended on the percentage of the cibarium volume exploited for suction: if the entire volume were used, velocities were in the range of meters per second. In contrast, velocities on the order of those found in the literature (about 10 cm/s) were attained if only 5% of the cibarium volume were exploited. Simulated bacterial colonization of the foregut was analyzed in relation to hydrodynamics and pressure needed for insects to ingest. Our model is designed to represent the diameter reduction of the food canal in both insect species when infected with X. fastidiosa . Results indicated that full bacterial colonization significantly increased the mean sap-sucking flow velocity. In particular, the colonization increased the maximum section-averaged velocity in the G. atropunctata more than two times and the net pressure needed to mantain the flow in the precibarium when colonized is relevant (about 0.151 MPa) if compared to a standard xylem sap tension (1 MPa). Bacterial colonization also influenced the sucking process of the G. atropunctata, by hindering the formation of a recirculation zone (or eddy), that characterizd the flow in the distal part of the precibarium when bacteria were absent. On the other hand, considering the pressure the insect must generate to feed, X. fastidiosa colonization probably influences fitness of the G. atropunctata more than that of P. spumarius .